Clinical and histopathological features of myeloid neoplasms with concurrent Janus kinase 2 (JAK2) V617F and KIT proto‐oncogene, receptor tyrosine kinase (KIT) D816V mutations. (1st June 2021) - Naumann, Nicole; Lübke, Johannes; Shomali, William; Reiter, Lukas; Horny, Hans‐Peter; Jawhar, Mohamad; Dangelo, Vito; Fabarius, Alice; Metzgeroth, Georgia; Kreil, Sebastian; Sotlar, Karl; Oni, Claire; et al.
Summary: We report on 45 patients with myeloid neoplasms and concurrent Janus kinase 2 ( JAK2 ) V617F and KIT proto‐oncogene, receptor tyrosine kinase ( KIT ) D816V ( JAK2 pos . / KIT pos . ) mutations, which are individually identified in >60% of patients with classical myeloproliferative neoplasms (MPN) and >90% of patients with systemic mastocytosis (SM) respectively. In SM, the concurrent presence of a clonal non‐mast cell neoplasm [SM with associated haematological neoplasm (SM‐AHN)] usually constitutes a distinct subtype associated with poor survival. All 45 patients presented with a heterogeneous combination of clinical/morphological features typical of the individual disorders (e.g. leuco‐/erythro‐/thrombocytosis and elevated lactate dehydrogenase for MPN; elevated serum tryptase and alkaline phosphatase for SM). Overlapping features identified in 70% of patients included splenomegaly, cytopenia(s), bone marrow fibrosis and additional somatic mutations. Molecular dissection revealed discordant development of variant allele frequency for both mutations and absence of concurrently positive single‐cell derived colonies, indicating disease evolution in two independent clones rather than monoclonal disease in >60% of patients examined. Overall survival of JAK2 pos . / KIT pos . patients without additional somatic high‐risk mutations [HRM, e.g. in serine and arginine‐rich splicing factor 2 ( SRSF2 ), additional sex combs like‐1 ( ASXL1 ) or Runt‐related transcription factor 1 ( RUNX1 )] at 5 years was 77%, indicating that the mutual impact of JAK2 V617F and KIT D816V on prognosis is fundamentally different from the adverse impact of additional HRM in the individual disorders.